2021
DOI: 10.1186/s40659-021-00367-x
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects of entomopathogenic fungi on control of the pest Lobesia botrana and the pathogenic fungus Eutypella microtheca on grapevine

Abstract: Background Entomopathogenic fungi (EPF) are the natural enemies of insect pests. Nevertheless, research on the use of EPF for simultaneous prevention of pest and disease agents on the same crop is limited. In this study, we explored the potential dual effects of three strains of the EPF Metarhizium anisopliae on the control of detrimental agents of Vitis vinifera L., including different developmental stages (larvae, pupae, and adult) of the insect pest Lobesia botrana and the phytopathogenic fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Also, we assessed the feeding preference of R. nu, a lepidopteran pest of soybean crops. Some species of entomopathogenic fungi, such as B. bassiana, Metarhizium brunneum, M. anisopliae, Lecanicillium lecanii, and Isaria javanica, are effective in controlling certain phytopathogenic fungi and stramenopiles, including Rhizoctonia solani, Pythium myriotylum, Sphaerotheca fuliginea, Botrytis cinerea, Fusarium oxysporum, Colletotrichium, Phytophthora, and Plasmopara viticola [19,26,27,31,[47][48][49][50][51]. As far as we are concerned, this is the first study to analyze the antagonistic effects of M. anisopliae and B. bassiana on M. phaseolina.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we assessed the feeding preference of R. nu, a lepidopteran pest of soybean crops. Some species of entomopathogenic fungi, such as B. bassiana, Metarhizium brunneum, M. anisopliae, Lecanicillium lecanii, and Isaria javanica, are effective in controlling certain phytopathogenic fungi and stramenopiles, including Rhizoctonia solani, Pythium myriotylum, Sphaerotheca fuliginea, Botrytis cinerea, Fusarium oxysporum, Colletotrichium, Phytophthora, and Plasmopara viticola [19,26,27,31,[47][48][49][50][51]. As far as we are concerned, this is the first study to analyze the antagonistic effects of M. anisopliae and B. bassiana on M. phaseolina.…”
Section: Discussionmentioning
confidence: 99%
“…were highly effective in infecting and killing of Lobesia botrana (Denis and Schiffermüller) in vitro, but their effectiveness significantly decreased under natural conditions, with noticeable differences between different seasons. 13 There is also growing evidence that EPF can colonize plant tissues, promote plant growth, and reduce pest damage. 14 Furthermore, the endophytic colonization can effectively protect EPF from adverse environmental factors such as UV radiation and low humidity.…”
Section: Introductionmentioning
confidence: 99%
“…Similar observations showed that three strains of Metarhizium anisopliae (Metsch.) were highly effective in infecting and killing of Lobesia botrana (Denis and Schiffermüller) in vitro , but their effectiveness significantly decreased under natural conditions, with noticeable differences between different seasons 13 . There is also growing evidence that EPF can colonize plant tissues, promote plant growth, and reduce pest damage 14 .…”
Section: Introductionmentioning
confidence: 99%